1999
DOI: 10.1089/107999099314171
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Interferon-Induced Expression of MxA mRNA in Peripheral Blood Mononuclear Cells with the Response of Patients with Chronic Active Hepatitis C to IFN-alpha Therapy

Abstract: MxA, a protein with selective activity against certain viruses, is an accepted specific indicator of type I interferon (IFN) activity. We have developed an internally controlled quantitative-competitive PCR to measure the amounts of MxA mRNA expressed in peripheral blood mononuclear cells (PBMC). This assay is more sensitive, quantitative, and easily applied to serial clinical samples than previously described methods. We have applied this assay retrospectively to 27 patients with chronic active hepatitis C gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Clinical studies have also suggested that those who respond to interferon-a treatment express increased amounts of MxA mRNA during treatment. 6 Hijikata et al 23 describe a second SNP at position À123 from the transcription start site, which is in close linkage disequilibrium with the SNP at position À88, and was therefore ignored in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have also suggested that those who respond to interferon-a treatment express increased amounts of MxA mRNA during treatment. 6 Hijikata et al 23 describe a second SNP at position À123 from the transcription start site, which is in close linkage disequilibrium with the SNP at position À88, and was therefore ignored in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, MxA mRNA levels have been reported to increase significantly after initiation of interferon therapy only in those who ultimately respond to treatment. 6 Upon binding to dsRNA, OAS-1 catalyses the formation of 2 0 -5 0 -linked oligoadenylate and activates RNAseL, which breaks down viral and cellular RNA. 7,8 PKR is also activated by dsRNA; this leads to the phosphorylation of its substrate, eIF2a, which inhibits the guanosine nucleotide exchange factor, eIF2b, and halts viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…MxA expression in PBMCs has been reported to be a highly specific and reliable marker for type I IFN bioactivity during IFN treatment or viral infections [Jakschies et al, 1994;Roers et al, 1994;Chieux et al, 1998;Meier et al, 2000;Pachner et al, 2003]. Furthermore, MxA has been used as a predictive marker of sustained antiviral response in chronically HCV-infected patients undergoing IFN therapy [Antonelli et al, 1999;Fernandez et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…9 Other compelling evidence suggests that SR patients do have increased MX1 mRNA production and elevated MX1 protein level during treatment. 10 Thus, the pharmacogenetic and experimental findings are internally and externally consistent with a convincing causal relationship.…”
Section: Confirmedmentioning
confidence: 61%